Sustainability of higher education institutions: Case study on cyber attacks (Global Business Management Review (GBMR), 2023)
Institution (HEI). The study adopted a qualitative methodology, employing a single case study as approach. A single case study is a method established to provide insightful examination of inquiries based on an inductive process of data collection, which is appropriate for this study. The study used purposive sampling as technique in selecting the fourteen interviewees. In addition, relevant documents and observation were also conducted to confirm the validity of the data gathered. Using a thematic analysis of qualitative methodology, the findings revealed sustainability of HEI depends on how HEI counter cyber-attacks. Most important, the finding revealed eight themes of cyber-attacks, they are: Malware, Ransom attack, WannaCry, Defacement, Altered content, Denial of service, Dictionary attack and Users negligence. The findings would be useful for HEI in data protection. The empirical findings of this study reflects that HEI is vulnerable to cyber-attacks thus it is imperative for HEI management to govern and tighten their cybersecurity. The findings of this study suggest novel guidance to design security measures that could balance the open system and control security.